Remote sensing Satellites and its application for agricultural development – Technical Aspect - Sivabalan, KR; Ramaraj, E (International Journal of Computer Sciences and Engineering, 2025)
Remote sensing is the escalating field in the ultimate modern world. It helps to the society in various aspects. Digital communication reaches the highest level with the help of remote sensing. Water development department works effectively with the remote sensitivity support. Not only has the digital division, Remote sensing also plays a major role in the advancement of food production and agriculture for human development. Agriculture is the backbone for every country. Agriculture development is one of the deciding factors for national development. Agriculture helps to increase domestic production and it leads to eliminating the problems of food shortages. Remote sensing plays a vital role in agriculture development like Crop production forecasting, Assessment of crop damage and crop progress, Crop Identification, Crop acreage estimation and etc. now a day’s crop required level water irrigation and crop disease identification was also done with the help of remote sensing. Every country shows the interest to launch the satellite for agriculture development. This paper helps to analyze the agriculture satellites technology and the remote sensing application for agriculture development